Expressions of Sceptical Topoi in (Late) Antique Judaism - Kiperwasser, Reuven; Herman, Geoffrey (Studies and Texts in Scepticism, 2021)
This volume of collected essays seeks to tackle the question of scepticism in an Early Jewish context, including Ecclesiastes and other Jewish Second Temple works, rabbinic literature, and reflections of Jewish thought in early Christian and patristic writings.